"IT'S TOO MUCH!": VICTIMS OF GENDER-BASED VIOLENCE ENCOUNTER THE MOROCCAN STATE. (February 2020) - Žvan Elliott, Katja
Abstract: By using the narrative approach and linking it to feminist research ethics and critical race methodology, this article seeks to understand how non-literacy and poverty hinder low-income women's access to justice and how these women experience the Moroccan state. The state here acts as an oppressive and marginalizing entity in women's lives, but also offers the potential for empowerment. This ethnographic study tells the stories of three victims of gender-based violence to demonstrate that the state needs to (1) set up an efficient and responsive infrastructure for those lacking know-how and money; (2) institute proper training of state agents for implementation of laws and to prevent them from acting on personal opinions and attitudes with regard to women's rights; and (3) strengthen procedures so that state agents can respond expeditiously to the needs and grievances of citizens.